Phytochemical Screening, Antibacterial Activity Against Periodontopathic Bacteria – Porphyromonas gingivalis and Aggregatibacter actinomycetemcomitans and HPLC of Opuntia ficus Fruit Extracts - Syed Wali Peeran; Wael Ibraheem; Hytham Fageeh; Hammam Ibrahim Fageeh; Syed Nahid Basheer; Nagabhushana Doggalli; Mohammad Nazish Alam (Natural Resources for Human Health, 2026)
The present study aimed to screen the phytochemicals, evaluate antibacterial efficacy of Opuntia ficus against periodontopathic bacteria, Porphyromonas gingivalis and Aggregatibacter actinomycetemcomitans using in-vitro assays, and conduct high-performance liquid chromatographic (HPLC) analysis. Using different solvents, like ethanol, ethyl acetate, n-hexane, and chloroform, extractions of the ficus powders were carried out using standard Soxhlet extraction methods. Phytochemical analysis, total phenolic contents, antibacterial activity, and high-performance liquid chromatographic (HPLC) analysis of Opuntia ficus extracts were investigated. Among the solvents, the most predominant phytoconstituents (flavonoids and phenols) were found in the ethanolic extract of Opuntia ficus. The total phenolic contents (TPC) in Opuntia ficus extracts varied, with the ethanol extract exhibiting the highest TPC at 63.3 mg GAE/g. Compared to standard antibiotics such as chloramphenicol (C), tetracycline (TE), and vancomycin (VA), the solvent extracts (n-hexane, ethyl acetate, and chloroform) from Opuntia ficus showed smaller inhibitory zone sizes against all tested bacteria. However, ethanol extract showed a significantly similar inhibitory zone when compared to the antibiotic ciprofloxacin (p